Kinetics of Free Fatty Acid Esterification in Used Cooking Oil Using Ion Exchange Resin as Catalyst - Sumaiya, Zainal Abidin; Vladisavljević, Goran T.; Saha, Basudeb (2014)
A kinetic study of free fatty esterification was carried out using Purolite D5081 as a catalyst. Esterification reaction was carried out using 1.25% (w/w) catalyst loading, 6:1 methanol to oil feed mole ratio, 350 rpm stirring speed and reaction temperatures ranging from 323 - 335 K. The experimental data from the esterification reaction were fitted to three kinetic models: Pseudo Homogeneous (PH), Eley-Rideal (ER) and Langmuir-Hinshelwood-Hougen-Watson (LHHW)models. A built-in ODE45 solver in MATLAB 7.0 was used to numerically integrate the differential molar balances describing the concentration of FFA in the system.